A escrita nos telefones móveis: uma análise à luz da abordagem sociointeracionista da linguagem. - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
The aim of this study is to investigate, in its principal aspect, the way in which occurs the process of interaction through writing emerging from the use of mobile phones. The research is considered as a field research, making use of questionnaire in order to investigate the profile of mobile technology users. In addition to the questionnaires, the corpora for analysis were obtained by observing a group in an instant messaging application for mobile phones WhatsApp, using the virtual ethnography proposed by Hine (2000). The sample is composed of undergraduate students of the second semester in Journalism and the fourth semester in Communication - Public Relations, of Federal University of Amazonas. It is generally used as theoretical support the sociointeractionist approach of language, which finds its assumptions in Bakhtin. It is used as corpora analysis tool the perspective of Conversation Analysis in Marcuschi and Interactional Sociolinguistics in Goffman. The analysis of the corpora of the research is guided by the research of how to configure the essential elements that enable verbal interaction. It analyzes, then, the organizational structure, by checking the discourse topic, the conversational turn, conversational sequences, the recasting activity (correction), and politeness, looking for similarities and differences between the uses of strategies in two planes, real and digital, face to face and virtual. Analyzing the digital conversation and the face to face conversation, it was noticed that some essential elements that enable verbal interaction can be used equally in both media, with, however, some own conversational strategies of digital media.
Keywords: Linguagem; Escrita; Telefones móveis; Sociointeracionismo; Language; Writing; Mobile phones; Sociointeractionism; LINGUÍSTICA, LETRAS E ARTES: LETRAS